Research handbook on the theory and practice of international lawmaking - Brölmann, Catherine; Radi, Yannick (Research handbooks in international law, 2016)
Introduction: International lawmaking in a global world / Catherine Brölmann and Yannick Radi -- State consent as foundational myth / Wouter G. Werner -- Subjects and actors in international lawmaking : the paradigmatic divides in the cognition of international norm generating processes / Jean d'Aspremont -- Transnational lawmaking / Dennis Patterson -- Contemporary theories and international lawmaking / Ingo Venzke -- Lawmaking by treaty : negotiation of agreements and adoption of treaty texts / Kirsten Schmalenbach -- Lawmaking by treaty : conclusion of treaties and evolution of a treaty regime in practice / Daniel Costelloe and Malgosia Fitzmaurice -- The emergence of customary international law : between theory and practice / Omri Sender and Michael Wood -- Relying on general principles in international law / Beatrice I. Bonafé and Paolo Palchetti -- Institutional lawmaking : the emergence of a global normative web / Ramses A. Wessel -- International judicial lawmaking / Gleider I. Hernandez -- Domestic judicial lawmaking / Antonios Tzanakopoulos -- Quasi-judicial bodies / Mara Tignino -- International lawmaking by hybrid bodies : the case of financial regulation / Michael S. Barr -- International lawmaking and civil society / Barbara K. Woodward -- Lawmaking by scholars / Jörg Kammerhofer -- The making of international human rights law / Vassilis P. Tzevelekos -- The making of international criminal law / Sergey Vasiliev -- The making of international trade law / Mary E. Footer -- The making of international environmental law / Francesca Romanin Jacur -- The making of international natural resources law / Owen McIntyre